Model studies on recycled whole rubber tyre reinforced granular fillings on weak soil - Geckil, Tacettin; Sarici, Talha; OK, Bahadir (Revista de la Construcción. Journal of Construction, 2022)
The main purpose of this study is to determine the stress-strain behaviour of a rigid circular footing placed on recycled rubber tyre-reinforced granular filling built on weak soil. For this purpose, model plate loading tests were carried out on reinforced/unreinforced granular filling built with natural aggregates (NA) or construction and demolition waste materials (CDW). The rubber tyre used for reinforcement has become a waste material by completing its service life but it has retained its typical cylindrical shape. In model plate loading tests, the effects of the granular fillings, the type of fillings material and the placement of whole rubber tyre and/or geotextile in the granular fillings were investigated. Depending on the results of tests, it was determined that the bearing capacity was increased by reinforcing with the rubber tyre and/or the geotextile. Furthermore, it was specified that the highest increase in bearing capacity was occurred case of by reinforcing with the geotextile together with the rubber tyre of the granular filling. The CDW and the NA fills reinforced with geotextile together with the rubber tyre increased the bearing capacity of weak soils by 6.59 and 8.49 times, respectively, for the 5% deformation ratio. On the other hand, it was reported that although the bearing capacity of the NA was higher than that of the CDW, the bearing capacity of the reinforced CDW approached that of the NA.